Inspired by Sharky Kesa

n = 1729 2017 k = 1 n ( k + n k ) \large \displaystyle \prod_{n=1729}^{2017} \sum_{k=1}^{\infty} \dfrac{n}{\binom{k+n}{k}}

If the above expression is the form of A B \dfrac AB , where A A and B B are coprime positive integers, find A + B A+B .


The answer is 3745.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rohit Udaiwal
Mar 6, 2016

First note that n = 1729 2017 k = 1 n ( k + n k ) = n = 1729 2017 n k = 1 1 ( k + n n ) [ ( a b ) = ( a a b ) ] . \displaystyle \prod_{n=1729}^{2017} \sum_{k=1}^{\infty} \dfrac{n}{\binom{k+n}{k}}=\prod_{n=1729}^{2017} n\cdot \color{#3D99F6}{\sum_{k=1}^{\infty} \dfrac{1}{\binom{k+n}{n}}}\quad \quad \quad \quad \quad \left[\because \binom{\color{magenta}{a}}{\color{#D61F06}{b}}= \binom{\color{magenta}{a}}{\color{magenta}{a}-\color{#D61F06}{b}}\right].

Denoting the highlighted \color{#3D99F6}{\text{highlighted}} series by S \color{#3D99F6}{\mathcal{S}} ,we have

S = k = 1 1 ( k + n n ) = k = 1 1 ( k + 1 ) ( k + 2 ) ( k + n ) n ! = n ! k = 1 1 ( k + 1 ) ( k + 2 ) ( k + n ) = n ! n 1 k = 1 ( 1 ( k + 1 ) ( k + 2 ) ( k + n 1 ) 1 ( k + 2 ) ( k + 3 ) ( k + n ) ) = n ! n 1 ( 1 2 3 n 1 3 4 ( n + 2 ) + 1 3 4 ( n + 2 ) ) [ Telescopic Series ] = n ! n 1 1 n ! = 1 n 1 \begin{aligned} \color{#3D99F6}{\mathcal{S}}=&\displaystyle \sum_{k=1}^{\infty} \dfrac{1}{\binom{k+n}{n}}=\sum_{k=1}^{\infty} \dfrac{1}{\frac{(k+1)(k+2)\ldots(k+n)}{n!}} \\ =& n! \displaystyle \sum_{k=1}^{\infty} \dfrac{1}{(k+1)(k+2)\ldots (k+n)} \\ =& \dfrac{n!}{n-1} \displaystyle \sum_{k=1}^{\infty} \left(\dfrac{1}{(k+1)(k+2)\ldots(k+n-1)}-\dfrac{1}{(k+2)(k+3)\ldots(k+n)}\right) \\ =& \dfrac{n!}{n-1}\left(\dfrac{1}{2\cdot3\cdot\ldots\cdot n}-\dfrac{1}{3\cdot4 \cdot\ldots\cdot (n+2)}+ \dfrac{1}{3\cdot4 \cdot\ldots\cdot (n+2)}- \ldots\right) \quad \quad [\small{\color{forestgreen}{\text{Telescopic Series}}}] \\ =&\dfrac{n!}{n-1}\cdot \dfrac{1}{n!} = \dfrac{1}{n-1} \end{aligned} n = 1729 2017 k = 1 n ( k + n k ) = n = 1729 2017 n n 1 Telescopic Series = 1729 1728 1730 1729 2017 2016 = 2017 1728 \large{\therefore \displaystyle \prod_{n=1729}^{2017} \sum_{k=1}^{\infty} \dfrac{n}{\binom{k+n}{k}}=\prod_{n=1729}^{2017} \dfrac{n}{n-1}} \\ \small{\color{forestgreen}{\text{Telescopic Series}}} \\ =\dfrac{\color{turquoise}{1729}}{\color{#EC7300}{1728}}\cdot \dfrac{\color{#E81990}{1730}}{\color{turquoise}{1729}}\cdot \ldots \cdot \dfrac{\color{#20A900}{2017}}{\color{#624F41}{2016}}\\ =\large{\boxed{\dfrac{\color{#20A900}{2017}}{\color{#EC7300}{1728}}}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...